Urban Forests as Nature-Based Solutions for Climate Resilience and Human Well-Being in Urban Landscapes. - Saroinsong, Fabiola B.; Patinggi, Febi F.; Pangemanan, Euis F. S.; Nurmawan, Wawan; Kalangi, Josephus I. (Jurnal Agroekoteknologi Terapan (JAT), 2026)
Rapid urban expansion has increased environmental pressures in cities, including rising urban temperatures, declining air quality, higher stormwater runoff and flood risk, and growing public health concerns. Nature-based solutions have gained attention as cost-effective and multifunctional approaches to address these challenges, with urban forests representing one of the most strategic forms of green infrastructure. This study reviews recent scientific evidence on the role of urban forests as nature-based solutions for strengthening climate resilience and improving human well-being in urban landscapes. A structured literature review was conducted using Scopus, Web of Science, and Google Scholar, focusing on peer-reviewed journal articles published between 2021 and 2025 and indexed with a DOI. Findings were synthesized thematically across key ecosystem service pathways, including urban heat regulation, stormwater and runoff control, carbon storage and sequestration, air quality improvement, and wellbeing-related benefits. The reviewed literature indicates that urban forests contribute to climate adaptation by reducing heat exposure through shading and evapotranspiration and by supporting stormwater regulation through rainfall interception and improved infiltration. Urban forests also contribute to climate mitigation through carbon storage and ongoing sequestration, while providing co benefits for human health through recreation opportunities, psychological restoration, and improved quality of life. However, effectiveness depends on long term canopy continuity, appropriate species selection, maintenance capacity, and governance arrangements, with common challenges including limited land availability, funding constraints, and unequal access to green spaces. Overall, urban forests function as multifunctional nature-based infrastructure that can enhance urban resilience and human wellbeing when integrated into long-term planning and participatory management. Keywords: climate resilience, ecosystem services, human wellbeing, nature-based solutions, urban forest